2015
DOI: 10.1016/j.jpolmod.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Financial shocks and the real economy in a nonlinear world: From theory to estimation

Abstract: We examine the inter-linkages between financial factors and real economic activity. We review the main theoretical approaches that allow financial frictions to be embedded into general equilibrium models. We outline, from a policy perspective, the most recent empirical papers focusing on the propagation of exogenous shocks to the economy, with a particular emphasis on works dealing with time variation of parameters and other types of nonlinearities. We then present an application to the analysis of the changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The body of evidence on the impact of systemic stress on the (real) economy is more limited than for the financial stress. In this subsection, I focus on studies that use the CISS (see Chatterjee idr., 2017;Chavleishvili & Kremer, 2017;Chavleishvili & Manganelli, 2019;Dajčman et al, 2020;Hartmann et al, 2013;Holló et al, 2012;Kremer, 2016a;Silvestrini & Zaghini, 2015). Holló et al (2012) and Kremer (2016a) D. Romih: The Impact of Systemic Stress in the Euro Area on Bilateral Exports of Goods studied the impact of systemic stress on industrial production in the euro area.…”
Section: The Impact Of Systemic Stress On the (Real) Economymentioning
confidence: 99%
“…The body of evidence on the impact of systemic stress on the (real) economy is more limited than for the financial stress. In this subsection, I focus on studies that use the CISS (see Chatterjee idr., 2017;Chavleishvili & Kremer, 2017;Chavleishvili & Manganelli, 2019;Dajčman et al, 2020;Hartmann et al, 2013;Holló et al, 2012;Kremer, 2016a;Silvestrini & Zaghini, 2015). Holló et al (2012) and Kremer (2016a) D. Romih: The Impact of Systemic Stress in the Euro Area on Bilateral Exports of Goods studied the impact of systemic stress on industrial production in the euro area.…”
Section: The Impact Of Systemic Stress On the (Real) Economymentioning
confidence: 99%
“…Consistent with previous findings, their studies suggest that the euro area needs to rethink some of its policies. Hartmann et al (2013) and Silvestrini and Zaghini (2015) studied the impact of systemic stress on GDP growth in the euro area in stress and non-stress regimes. They found that systemic stress negatively affects GDP growth only in stress regimes.…”
Section: The Impact Of Systemic Stress On the (Real) Economymentioning
confidence: 99%
“…The theoretical framework of Bernanke et al (1999) and Kiyotaki and Moore (1997) can help explain how endogenous developments in financial markets amplify shocks to the real economy (Aprigliano & Liberati, 2021; Miglietta & Venditti, 2019). The interaction between financial factors and real economic activity has thus assumed a pivotal role in econometric tools for modeling and forecasting purposes (Borio et al, 2020; Crump et al, 2021; Claessens et al, 2012; Paccagnini, 2019; Silvestrini & Zaghini, 2015).…”
Section: Introductionmentioning
confidence: 99%